Study on the Learning Outcomes of Mathematics Affecting the Learning of Medical Technical Students at the University of Health Sciences, Lao PDR - VOLLASIN, Xayphasith; SIRISACK2, Sackmone; LILIANOU, Lisatteur; PHANALASY, Oudone; MOUNLASAN, Thavisone (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purpose of this research was to environmental for learning mathematics, teaching quality of math teachers, attitude towards learning mathematics, mathematical learning behavior, motivation and success in studying mathematics and family situation were the affecting on mathematics learning of Medical Technology Students at University of Health Sciences, Vientiane Capital. This study was analyzed in two ways: 1. The method of analyzing statistical data is to use Microsoft Excel to help the average, percentage, average frequency and other statistical values ​​of the personal data section of the respondents and some aspects of students' ability to learn mathematics; 2. The method of analyzing data with mathematical models is to use Microsoft Excel to analyze and calculate the matrix coefficients, find the largest static value and the static vector velocity that corresponds to the largest static matrix data query. Researchers on Mathematics results affecting the learning outcome of Medical Technology Students at University of Health Sciences, Lao PDR: The environment of learning mathematics and Mathematical learning behavior at the intermediate level; The teaching quality of math teachers, Attitudes towards learning mathematics, Motivation to succeed in math and Family situations on upper intermediate levels. Therefore, it was concluded that the overall level of Mathematics results affecting the learning outcome of Medical Technology Students at University of Health Sciences, Lao PDR, in the six components was moderate at 3.5022.